Philosophy: The First Science - Rai , Bimalendra (Journal of Innovation in Academia, 2024)
There is a bifurcation between philosophy and science: a derogative word, impractical and dead discipline; and a laudatory term for objectivity, and utmost necessity of the modern world respectively. Many articles highlight higher paying jobs and enrollment in STEM fields indicating it has a solely existing discipline for a long; however, philosophy makes it possible for science to exist, including language and communication a lineage. This paper shows before science, philosophy came into play with objectivity facts; and applications, meaning philosophy was the first science. The fallacy of science as empirical and superior for its attainability measurement is countered through backings. The rebuttals and qualifiers expose such fallacy, failure of Newtonian science (three-body problems), and quantum emersion, for instance, break its objectivity and truth; which occur is the interplay of time and relevance like philosophy; however, unlike pure science, philosophy holds its ground firm for more than two millennia. The ether of philosophy, unlike science, goes beyond stating reality or truth, rather for a much larger implication to seek. Thus, science is the ripest of the ripe and most delicious of the delicious fruit of philosophy.